2020
DOI: 10.3389/fphys.2020.01032
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Response of Serum Cartilage Oligomeric Matrix Protein to Different Types of Impact Loading Under Normal and Artificial Gravity

Abstract: Microgravity during long-term space flights induces degeneration of articular cartilage. Artificial gravity through centrifugation combined with exercise has been suggested as a potential countermeasure for musculoskeletal degeneration. The purpose of this study was to investigate the effect of different types of impact loading under normal and artificial gravity conditions on serum concentrations of cartilage oligomeric matrix protein (COMP), a biomarker of cartilage metabolism. Fifteen healthy male adults (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 70 publications
(94 reference statements)
0
8
0
Order By: Relevance
“…Different types of exercise that target not only the cardiovascular system but also muscle and bone would probably be more suitable, for example the high-intensity jump training that proved to be very effective in maintaining muscle, bone and cardiovascular health in a previous long-term bed rest study (Kramer et al 2017a ). It was already demonstrated that jumping whilst being centrifuged is possible, albeit with reduced peak ground reaction forces and changes in the movement pattern that might lower the countermeasure efficacy (Dreiner et al 2020 ; Kramer et al 2020a ; Frett et al 2020 ). Hence, future studies are needed to (a) determine those exercise regimes that could be combined with AG exposure, and (b) disentangle the effects observed in studies combining centrifugation and exercise by comparing the effects of the combined intervention to the effects of exercise alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different types of exercise that target not only the cardiovascular system but also muscle and bone would probably be more suitable, for example the high-intensity jump training that proved to be very effective in maintaining muscle, bone and cardiovascular health in a previous long-term bed rest study (Kramer et al 2017a ). It was already demonstrated that jumping whilst being centrifuged is possible, albeit with reduced peak ground reaction forces and changes in the movement pattern that might lower the countermeasure efficacy (Dreiner et al 2020 ; Kramer et al 2020a ; Frett et al 2020 ). Hence, future studies are needed to (a) determine those exercise regimes that could be combined with AG exposure, and (b) disentangle the effects observed in studies combining centrifugation and exercise by comparing the effects of the combined intervention to the effects of exercise alone.…”
Section: Discussionmentioning
confidence: 99%
“…The DLR short-arm human centrifuge has a radius of 3.8 m [for a schematic representation of the centrifugation see Fig. 2 , for more details on the system see previous publications using this centrifuge (Kramer et al 2020a ; Dreiner et al 2020 )]. The participant's position with respect to the center of rotation as well as the rotational speed of the centrifuge were adjusted to achieve an acceleration of 1 g at the estimated center of mass and approximately 2 g at the feet.…”
Section: Methodsmentioning
confidence: 99%
“…This might also explain the observed difference in the extent of increase between jumping and running when specific biomarkers (COMP and MMP-3) were tested. For running exercise (~ 2422 impacts per leg), the number of impacts per leg was almost tenfold higher than for jumping exercise (~ 254 impacts per leg) 44 . In addition, between each jumping series, which lasted approximately 12 s, a resting period of approximately 75 s was included, and regeneration or compensation of the biomarker concentration may occur even during this relatively short resting period, resulting in a less measurable increase in serum concentration compared to running exercise.…”
Section: Discussionmentioning
confidence: 84%
“…As an alternative to human centrifugation, the use of chronic artificial gravity in large rotating platforms to counteract microgravity pathologies is connected to several engineering challenges, but likely seems to be the most physiological solution [ 91 , 92 ]. In short arm human centrifuges, exposure to artificial gravity alone without further exercise is not sufficient to maintain the muscle mass, but studies testing the combined effects of artificial gravity and exercise are currently conducted [ 93 , 94 , 95 ]. Dreiner et al [ 93 ] studied the effect of different types of impact loading under normal and artificial gravity conditions on serum COMP concentrations.…”
Section: Countermeasuresmentioning
confidence: 99%
“…In short arm human centrifuges, exposure to artificial gravity alone without further exercise is not sufficient to maintain the muscle mass, but studies testing the combined effects of artificial gravity and exercise are currently conducted [ 93 , 94 , 95 ]. Dreiner et al [ 93 ] studied the effect of different types of impact loading under normal and artificial gravity conditions on serum COMP concentrations. Under Earth gravity, jumping and running resulted in a significantly higher increase in COMP serum level 30 min after impact loading than impact loading under artificial gravity.…”
Section: Countermeasuresmentioning
confidence: 99%